PROMOSI PERPUSTAKAAN DI UNIT PELAKSANA TEKNIS (UPT) PERPUSTAKAAN UNIVERSITAS LANCANG KUNING - Yuhelmi, Yuhelmi (Aksara Public, 2017)
This study aims to reveal "How Promotion has been done UPT Library staff University of Lancang Kuning Pekanbaru in increasing the number of visitors. This is done to see how the promotion is implemented, what promotion has or has not done by the library in increasing the number of visitors. In addition, as the end result, this research also aims to find out what promotion should be improved and maintained for future development to increase the number of visitors in the library. The method used is qualitative method. Respondents in this research are both permanent and honorary library staff who have been involved in library promotion activities. To support the result of research, the researcher interviewed the Head of Library. The final goal of this research is to reveal what promotion has been done and what the promotion can be applied in an effort to increase the number of visitors.